A Literature Review on Stress and Eating Disorders in Adolescents: Psychological and Behavioral Perspectives - Deviantony, Fitrio; Gani, Amelinda Nasywa Filial; Hariyanti, Fajar Dini; Adzahri, Hasbi Asyidiq (Al-Hijrah Indonesia, 2025)
Background: Stress affects adolescent health, often leading to unhealthy eating and increasing the risk of eating disorders, especially in young women. Academic pressures and body image concerns intensify stress-related eating. Interventions like mindfulness and nutrition education can support healthier coping and reduce eating disorders in youth. Purpose: The study aims to highlight the significant impact that stress can have on eating behaviors and to provide insights into how these factors are interconnected. Methods: A review of the literature from 2019 to 2024 was conducted as part of this research technique using PubMed and Science Direct, the keywords